Current Tax Risk in Romania and Possible Remedies - Attila Szora TAMAȘ; Ramona-Ionela HARAGUȘ; Gabriel Szora TAMAȘ; Alin IRIMIA (Finanţe: Provocările viitorului)
Following the controls carried out by the National Agency for Fiscal Administration (ANAF), the income from unidentified sources of individuals will be taxed by 70% (not only by 16%), as of 1 July 2024, the measure introduced by Law 296/2023. The tax procedure code (FCP) in Article 138 regulates the verification of the personal tax situation by the central tax authority. This article requires the tax authority to carry out certain preliminary activities before the start of the control itself. Risk analysis, notification of compliance and selection are the preliminary tasks. Loans made to the company to which a person has the capacity of associate will attract the attention of the tax authority, if their value exceeds the declared revenues. The study proposes the analysis of situations in which, loans between different parties, revenues obtained from virtual currency trading and sponsorship under Article 6 of Law no. 32/1994, constitute facts with fiscal risk. To this end, the used research methodology involved the identification and interpretation of the nationally regulated texts. The study identified current tax risks related to the situations mentioned in the previous paragraph and also proposed certain solutions regarding the fiscal risk.